2021
DOI: 10.1080/14992027.2021.2009923
|View full text |Cite
|
Sign up to set email alerts
|

Premium versus entry-level hearing aids: using group concept mapping to investigate the drivers of preference

Abstract: List of the different cluster names, their overall themes, total number of statements, example statements, and average bridging values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In contrast, previous studies did not provide evidence to suggest that premium HAs yield better self-reported real-world outcomes or laboratory outcomes (Cox et al, 2014;Johnson et al, 2016;2017;Plyler et al, 2021;Saleh et al, 2021). Although Wu et al (2019) found that premium HAs provided better speech understanding and sound localization in the laboratory, this improvement was not transferred to the real-world setting.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In contrast, previous studies did not provide evidence to suggest that premium HAs yield better self-reported real-world outcomes or laboratory outcomes (Cox et al, 2014;Johnson et al, 2016;2017;Plyler et al, 2021;Saleh et al, 2021). Although Wu et al (2019) found that premium HAs provided better speech understanding and sound localization in the laboratory, this improvement was not transferred to the real-world setting.…”
Section: Discussionmentioning
confidence: 79%
“…Those in more demanding listening environments reported significant improvement with premium HAs compared to those in less demanding sound environments. Also, the preference of using premium technology was found to be a factor in Cox et al (2016) , Plyler et al (2021) , and Saleh et al (2021) . These results indicate that candidacy for premium technologies and auditory ecology are highly relevant aspects that should be included in the HA provision process to improve current clinical procedures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation